2017
DOI: 10.1007/s10803-017-3127-z
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Information Source Preferences of Parents of Individuals with Autism Spectrum Disorder

Abstract: For parents of children with an Autism spectrum disorder (ASD), high quality, easily accessible information and a strong peer network can be the key to raising a happy, healthy child, and maintaining family well-being and emotional resilience. This article reports the findings of an anonymous survey examining the information source preferences for 935 parents of individuals with ASDs in North Carolina. Data indicates that parents show similar information seeking patterns across the age spectrum, that availabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 21 publications
2
50
0
3
Order By: Relevance
“…Instead, it is about the everyday life and parenting information needs and practices of people who share a uniting facet of identity (which is, at times, related to health). Because intersections (Crewshaw, ) among disability, race, and gender impact everyday information needs and practices (Gibson, Kaplan, & Vardell, ), the information worlds (Jaeger & Burnett, ) and everyday life information needs of mothers of people with disabilities often differ somewhat from those of other mothers (Walker, ).…”
Section: Phenomenon Of Interest and Research Questions Addressedmentioning
confidence: 99%
“…Instead, it is about the everyday life and parenting information needs and practices of people who share a uniting facet of identity (which is, at times, related to health). Because intersections (Crewshaw, ) among disability, race, and gender impact everyday information needs and practices (Gibson, Kaplan, & Vardell, ), the information worlds (Jaeger & Burnett, ) and everyday life information needs of mothers of people with disabilities often differ somewhat from those of other mothers (Walker, ).…”
Section: Phenomenon Of Interest and Research Questions Addressedmentioning
confidence: 99%
“…Compared to American parents of children with ASD (Gibson et al, 2017;Gibson & Kaplan, 2015), Chinese parents of children with ASD have similar information needs on independent living, puberty, policy and regulation, and language development. But they are in lack of official information sources such as national organizations, website and so on.…”
Section: Discussionmentioning
confidence: 99%
“…For parents of children with ASD, their health information behavior run through the whole process of raising children. Research has found that parents of younger children with ASD pay more attention to physical growth and education information, they communicate more with doctors and teachers, and their information sources decrease as their children grow up (Gibson et al, ). Parents of older children are more concerned about independent living ability, job training and higher education.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Goytia et al (2005) investigated public libraries' capacity to support cancer screening in underserved communities to reveal significant attitudinal barriers on the part of the library staff. Gibson, Kaplan, and Vardell (2017) found that "libraries were the least frequently selected source of information" for parents of individuals with Autism Spectrum Disorder. Similarly, Flaherty, Tayag, Lanier, and Minor (2014) found that not all public libraries provide credible information in response to the question "do vaccines cause autism?…”
Section: Introductionmentioning
confidence: 99%